Way Out West: Mapping Western Australia - Stratton, Jon; Beilharz, Peter (2016)
Western Australia, like Tasmania, can slip too easily off the map, a periphery on the periphery, its significance occluded by the hegemony of the eastern states of Australia. Yet Western Australia is core to Australia's economy, not least through mining, and through its proximity to Asia. The West is itself connected more closely to region, in both the local and transnational senses. Its tradition of secessionist thinking indicates a kind of exceptionalist culture. This is a difference which begs for explanation. This essay introduces some motifs and themes of this special issue of Thesis Eleven, entitled 'Way Out West: Mapping Western Australia'. It locates the West in some recent historical, geographical and narrative context. It gestures toward the biography of its editors, Jon Stratton and Peter Beilharz, and their locations spread across the west and east of the continent. It calls for further scrutiny of these, and other antipodes. © Thesis Eleven Pty, Ltd., SAGE Publications..